2019
DOI: 10.1093/ije/dyz239
|View full text |Cite
|
Sign up to set email alerts
|

Urban green space, tree canopy and prevention of cardiometabolic diseases: a multilevel longitudinal study of 46 786 Australians

Abstract: Background Cross-sectional studies suggest that more green space may lower the odds of prevalent diabetes, hypertension and cardiovascular diseases (CVD) in cities. We assess if these results are replicable for tree canopy exposure and then extend the study longitudinally to examine incident cardiometabolic outcomes. Methods The study was set in the Australian cities of Sydney, Wollongong and Newcastle. Total green space and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(58 citation statements)
references
References 22 publications
7
51
0
Order By: Relevance
“…Although our study was cross-sectional and used NDVI levels to estimate exposure, our findings may support those from 2 prospective cohort studies 15 , 32 that used different green space measures and 1 natural experiment study. 18 The first cohort study followed up 5112 Lithuanian adults for 4.4 years.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Although our study was cross-sectional and used NDVI levels to estimate exposure, our findings may support those from 2 prospective cohort studies 15 , 32 that used different green space measures and 1 natural experiment study. 18 The first cohort study followed up 5112 Lithuanian adults for 4.4 years.…”
Section: Discussionsupporting
confidence: 62%
“… 15 The second cohort study found that a larger tree canopy percentage was associated with a lower risk of incident CVD among 46 786 Australian adults. 32 In the natural experiment study, Donovan et al 21 analyzed longitudinal data from 156 146 women and examined the association between the loss of trees owing to an invasive forest pest and incident CVD. They reported that women living in areas with greater tree loss had an increased risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence has pointed towards a relationship between greenspace and physical or psychological health [ 1 , 2 , 3 ]. A number of metrics are used to quantify greenspace [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…While NDVI measures overall “greenness”, discretely marked green zones such as parks may represent public open spaces. The amount of tree canopy in such buffers has recently been shown to be more salient to health than other forms of greenspace [ 1 ]. Finally, even GSV-based metrics may have to be based on an optimal buffer size within which green exposure is measured.…”
Section: Introductionmentioning
confidence: 99%